Belief-Free Equilibria in Games With Incomplete Information - Hörner, Johannes; Lovo, Stefano (Econometrica, 2009)
We define belief-free equilibria in two-player games with incomplete information as sequential equilibria for which players' continuation strategies are best replies after every history, independently of their beliefs about the state of nature. We characterize a set of payoffs that includes all belief-free equilibrium payoffs. Conversely, any payoff in the interior of this set is a belief-free equilibrium payoff. The characterization is applied to the analysis of reputations. Copyright 2009 The Econometric Society.